A network application approach towards 5G and beyond critical communications use cases - Apostolakis, Konstantinos C.; Valera-Muros, Barbara; di Pietro, Nicola; Garrido, Pablo; del Teso, Daniel; Kamarianakis, Manos; Tomas, Pedro R.; Khalili, Hamzeh; Panizo, Laura; Zayas, Almudena Díaz; Protopsaltis, Antonis; Margetis, George; et al. (Frontiers in Communications and Networks, 2024)
Low latency and high bandwidth heralded with 5G networks will allow transmission of large amounts of Mission-Critical data over a short time period. 5G hence unlocks several capabilities for novel Public Protection and Disaster Relief (PPDR) applications, developed to support first responders in making faster and more accurate decisions during times of crisis. As various research initiatives are giving shape to the Network Application ecosystem as an interaction layer between vertical applications and the network control plane, in this article we explore how this concept can unlock finer network service management capabilities that can be leveraged by PPDR solution developers. In particular, we elaborate on the role of Network Applications as means for developers to assure prioritization of specific emergency flows of data, such as high-definition video transmission from PPDR field users to remote operators. To demonstrate this potential in future PPDR-over-5G services, we delve into the transfer of network-intensive PPDR solutions to the Network Application model. We then explore novelties in Network Application experimentation platforms, aiming to streamline development and deployment of such integrated systems across existing 5G infrastructures, by providing the reliability and multi-cluster environments they require.